1973
DOI: 10.1093/infdis/127.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Viruses Causing Common Respiratory Infections in Man

Abstract: Introducing a new hobby for other people may inspire them to join with you. Reading, as one of mutual hobby, is considered as the very easy hobby to do. But, many people are not interested in this hobby. Why? Boring is the reason of why. However, this feel actually can deal with the book and time of you reading. Yeah, one that we will refer to break the boredom in reading is choosing viruses causing common respiratory infections in man as the reading material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Further details concerning enteroviral diseases may be found in several general reviews on the role of nonpolio enteroviruses in human disease (11,44,64,70,88) and in reviews covering specialized topics such as viral myocardiopathies (26,49,51,88), coxsackievirus infections of newborns (26), virus diseases associated with cutaneous eruptions (106), respiratory disease viruses (38), congenital malformations associated with maternal viral infection (4), and the possible role of viruses in diabetes mellitus (16,75). Enteroviruses have also been reported to produce a persistent infection, particularly associated with a myalgic encephalomyelitis, also known as postviral fatigue syndrome (112).…”
Section: Resultsmentioning
confidence: 99%
“…Further details concerning enteroviral diseases may be found in several general reviews on the role of nonpolio enteroviruses in human disease (11,44,64,70,88) and in reviews covering specialized topics such as viral myocardiopathies (26,49,51,88), coxsackievirus infections of newborns (26), virus diseases associated with cutaneous eruptions (106), respiratory disease viruses (38), congenital malformations associated with maternal viral infection (4), and the possible role of viruses in diabetes mellitus (16,75). Enteroviruses have also been reported to produce a persistent infection, particularly associated with a myalgic encephalomyelitis, also known as postviral fatigue syndrome (112).…”
Section: Resultsmentioning
confidence: 99%
“…The nascent, cleavages, which have been assigned to host proteases in poliovirus infections (58,139) also occur in rhinovirus-infeetions. Successful inhibition of rhinovirus replication has been reported with increasing frequency in infected monolayers judging from the most recent reviews (42,53,127,132) and the Annual Reports in Medicinal Chemistry (3,25,26,67,111), the listings of recent Antiviral Chemotherapy Publications which appear on a bimonthly basis (116,117,118,119,120), and the information presented in 1.975 at the Symposium on Antivirals with Clinical Potential (84). These may represent, viral proteases, or activated cellular enzymes.…”
Section: Protein Synthesis and Proeessinflmentioning
confidence: 99%
“…However, at this time there are many gaps in our knowledge of this sequence. Reviews in "outline" form are also available (53,129). Despite these limitations, there have been recent advances, since the extensive review of STOTT and KILLINGTO~ (127), particularly in the areas of early virus-cell interaction and the processing of viral proteins, and an over-all view of rhinovirus replication is beginning to take shape.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the observed frequencies of these types have shown that some of them are very common among different populations and seem to infect children early in life, while others infect them later and are less frequent (Jackson & Muldoon, 1975). Many studies have been done to establish the frequencies of isolation and their role in causing disease.…”
Section: Introductionmentioning
confidence: 99%